Способ прогнозирования течения ишемической болезни сердца - Канская Н. В. Наталья Викторовна; Твердохлебов C. И. Сергей Иванович; Позднякова И. А. Ирина Анатольевна; Фёдорова Н. А. Нина Александровна; Пичугин В. Ф. Владимир Федорович; Канский А. В. Александр Викторович
опубл. 20.12.12, Бюл. № 35